A practical demonstration of autonomous ultrasonic testing for rail flaws inspection - He, Feiyang; Durazo-Cardenas, Isidro; Liu, Haochen; Rahman, Miftahur; Rahimi, Masoumeh; Starr, Andrew; Poulter, Michael (Cranfield University, 2022)
This study established the viability of autonomous ultrasonic inspections at the technology readiness level 5 (TRL 5). An autonomous ultrasonic rail inspection prototype was developed using commercially available ultrasonic instruments and an unmanned on-track vehicle platform consisting of a Clearpath's Warthog and a road-rail vehicle (RRV) trolley. The prototype was designed to travel back and forth on a segment of the test track during the test programme. Repeated fault checks were able to discover seeded artificial flaws at depths of 23 and 27 mm. The detection was indicated by an audio alarm triggered when the ultrasonic emissions exceeded the threshold of the detector gate. A plain text message sent over local area network (LAN) WIFI to a virtual server was also used to demonstrate the transmission of detection messages. The repeatability of the inspection prototype's positioning relative to the problem was confirmed using odometry, global navigation satellite system (GNSS), and positional measurements. The results of the three measurement methods were in good agreement, and the positioning inaccuracy varied between 3 and 7 cm. This study demonstrated the potential of autonomous ultrasonic checks and gave recommendations for further work and limitations.
11th International Conference on Through-life Engineering Services - TESConf 2022, 8-9 November 2022, Cranfield UK
Keywords: Autonomous; Ultrasonic; Rail; Inspection